2017
DOI: 10.1051/0004-6361/201629934
|View full text |Cite
|
Sign up to set email alerts
|

Flattening and surface-brightness of the fast-rotating star δ Persei with the visible VEGA/CHARA interferometer

Abstract: Context. Rapid rotation is a common feature for massive stars, with important consequences on their physical structure, flux distribution and evolution. Fast-rotating stars are flattened and show gravity darkening (non-uniform surface intensity distribution). Another important and less studied impact of fast-rotation in early-type stars is its influence on the surface brightness colour relation (hereafter SBCR), which could be used to derive the distance of eclipsing binaries. Aims. The purpose of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Concerning Vega, the authors concluded that the star rotates at V/V c 0.75 (Ω/Ω c 0.92) and that the inclination angle of its rotation axis is 4.8 o . The B-type star δ Per was observed with the VEGA/CHARA interferometer by Challouf et al [463], and the data were analyzed using a code of stellar rotation, CHARRON [464,465], in order to derive the stellar physical parameters. The estimated stellar flatness is R eq /R p = 1.121, the inclination angle i = 85 o and the velocity ratio V/V c 0.57.…”
Section: Interferometry Of Rotating Starsmentioning
confidence: 99%
“…Concerning Vega, the authors concluded that the star rotates at V/V c 0.75 (Ω/Ω c 0.92) and that the inclination angle of its rotation axis is 4.8 o . The B-type star δ Per was observed with the VEGA/CHARA interferometer by Challouf et al [463], and the data were analyzed using a code of stellar rotation, CHARRON [464,465], in order to derive the stellar physical parameters. The estimated stellar flatness is R eq /R p = 1.121, the inclination angle i = 85 o and the velocity ratio V/V c 0.57.…”
Section: Interferometry Of Rotating Starsmentioning
confidence: 99%